ANALYSIS OF PERFORMANCE AFFECTED BY LEADERSHIP, TRAINING, MOTIVATION AND COMPENSATION: THE CASE OF STARBUCKS COFFEE INDONESIA REGION 7 - Nur Aini Azizah; Aris Budiono (Jurnal Ekonomi, 2023)
This article analyses Starbucks Coffee employee performance in Region VII as influenced by leadership, training, motivation, and compensation variables. The Likert scale is used in compiling measurement instruments. We used 30 respondents for validity and reliability tests and 100 respondents for multiple linear regression statistical analysis with the application of SPSS-26 statistics to prove the simultaneous and partial influence hypothesis. We used the Roscoe method. The result of this study is that the three independent variables simultaneously influence the dependent variable. On partial influences, namely: leadership variables affect employee performance, motivation affects employee performance, training does not affect employee performance and compensation does not.